Desempenho e resistência imunológica do camarão Litopenaueus vannamei alimentado com uma dieta rica em B-1, 3/1,6-glucano e ácido L-ascórbico-2-monofosfato frente ao vírus da mionecrose infecciosa (IMNV) - Sabry Neto, Hassan (2007)
Since 2002, a new pathogen agent named Infectious Myonecrosis Virus (IMNV) has been causing significant economical losses in shrimp farms in NE Brazil. Contrary to vertebrates, shrimp do not possess an immunological system with an adaptative memory. However, they are equipped with an innate immune system with less complex defense responses. The present study aimed at determining the efficacy of high dosages of L-ascorbyl 2-monophosphate acid (VitC) in combination with a ß-1,3/1,6-glucan (BetG) on the survival, growth and immune responses of the shrimp Litopenaeus vannamei challenged with IMNV. The study was conducted in 30 tanks of 500 l, operated with clear water conditions and constant water renewal and aeration. Shrimp of 2.58 ± 0.39 g were stocked at 100 animals/m2 and reared for 10 weeks. The experimental design consisted of three treatments and three controls. Five tanks were designated for each treatment and control, as follows: Ref, IMNV- (IMNV negative) fed a commercial feed; Neg and Pos, IMNV- and IMNV+ (IMNV positive), fed an experimental feed with normal levels of L-ascorbyl 2-monophosphate (VitC, 250 mg/kg) deprived of BetG; VitC, IMNV+, fed an experimental feed with 1,160 mg/kg of VitC; VitCBetG, IMNV+, fed an experimental feed with 1,160 mg/kg of VitC and 600 mg/kg of BetG; and, BetG, IMNV+, fed an experimental feed with 1,000 mg/kg of BetG and normal levels of VitC. Experimental feeds were manufactured with laboratory equipment, while shrimp viral challenge occurred through oral administration of IMNV+ inoculum (1.82 x 103 copies of IMNV/μl RNA) during three consecutive days, twice a day. Per os challenge began on the 27th day of exposure to the experimental feeds when animals had reached between 4.93 g and 6.92 g in body weight. The total haemocyte count (THC), the total protein concentration and the relative activity of the phenoloxidase enzyme (PO) were evaluated in L. vannamei two days prior to the oral challenge (27th day of rearing), 17 days after the challenge (48th day of rearing) and at harvest (70th day of rearing). Reared shrimp were effectively contaminated with IMNV. Although 100% mortalities were not observed, animals were highly susceptible to the virus 29 days after the first day of infection. At harvest, shrimp reached a body weight between 9.07 ± 1.48 g (BetG) and 11.11 ± 1.86 g (Pos). Survival varied from a minimum of 22.8 ± 4.9% (VitC) to a maximum of 69.5 ± 5.7%. Shrimp body weight gains were continuous with weekly growth ranging from 0.56 g on the 14th day of culture to 0.77 g in the last week of culture. Shrimp weekly growth did not vary statistically between treatments. Survival reduced throughout the culture period, regardless of the treatment adopted. The THC showed a significant increase in all treatments after the per os challenge with IMNV (i.e., 48th day of culture). On this sampling day, the highest number of cells/mm3 were observed in treatments that were voluntarily challenged with IMNV, which were the ones that achieved the lowest final shrimp survival (Pos and VitC). Similarly, the non-challenged treatment (Ref) also displayed a significant increase in THC during the post-infection viral period. In general, the protein concentration and the relative activity of the phenoloxidase activity in shrimp serum did not change significantly throughout the culture period or between treatments. By this study it can be concluded that an inclusion of 600 mg/kg of ß- 1,3/1,6-glucan in a diet for the shrimp L. vannamei provided a significant increase in the species survival when exposed to IMNV. Conversely, the inclusion of 1,160 mg/kg of L-ascorbyl 2-monophosphate acid in diets for this species infected with IMNV did not result in a better growth or survival. In the present study, no signs of immunological fatigue or a detriment in growth could be detected when the species was continually exposed to a diet containing 600 mg/kg of ß-1,3/1,6-glucan.